Object-Oriented Programming Applied to the Finite Element Method Part I. General Concepts - Besson, Jacques; Foerch, Ronald (European Journal of Computational Mechanics, 1998)
This paper examines the application of object-oriented programming techniques to the finite element method. First a tool library is briefly presented: it includes mathematical objects such as vector, matrix and tensor, as well as generic types such as array, list and encapsulated pointer. Design patterns are then presented. They allow the defining of reusable implementation strategies which help to obtain a flexible extensible code. Finally the paper demonstrates the use of the different patterns in the case of objects describing finite elements and object representing material behaviors.